Decisions of the Supreme Court of Newfoundland : the reports, 1854-1864 - Newfoundland. Supreme Court (J.W. Withers, Queen's Printer, 1900)
The decisions of the Supreme Court of Newfoundland and Labrador. Most volumes include both case and topical indexes. Alternative title from spine.